The future of vaccination and herd immunity in the COVID-19 pandemic - Supriyadi, Supriyadi (MEDISAINS, 2021)
Since a year ago, pandemic covid 19 has entered Indonesia, and efforts to reduce and control have been carried out several programs, one of which is vaccination. The ideal projection is two direct strategies: hybrid distribution that combines active outreach into priority groups with passive distribution to the general public and single-dose distribution to as many populations as possible. The previous plan was to save a second dose as a backup. The proper fulfillment of vaccination needs in each population required to achieve herd immunity to stop the spread of the virus will vary, depending on the variant of the virus in circulation and the heterogeneous level of that population, also depending on the density and mobility of the population. In addition, the duration of protection provided by natural immunity and vaccine-induced immunity is not well established, and different vaccines can provide different durations and degrees of humoral and cellular immunity.